1999
DOI: 10.1016/s0194-5998(99)70127-0
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term impact of functional endoscopic sinus surgery on asthma

Abstract: Using objective and subjective criteria, we performed a study to assess the long-term impact of functional endoscopic sinus surgery (FESS) in patients with chronic rhinosinusitis and asthma at an average follow-up of 6.5 years. One hundred twenty patients who underwent FESS for chronic rhinosinusitis were followed up for an average of 6.5 years (range 6.0 to 10.6 years). Seventy-two (60%) patients responded to a follow-up questionnaire, and 30 (42%) of them reported a history of asthma. Subjective levels of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(52 citation statements)
references
References 15 publications
2
48
1
1
Order By: Relevance
“…They noted a reduction of corticosteroid medication following ESS. Senior et al [22] reported that ESS contributed to symptomatic improvement in bronchial asthma after long-term (mean 6.5 years) observation. However, they did not use any objective assessments such as pulmonary function tests.…”
Section: Discussionmentioning
confidence: 99%
“…They noted a reduction of corticosteroid medication following ESS. Senior et al [22] reported that ESS contributed to symptomatic improvement in bronchial asthma after long-term (mean 6.5 years) observation. However, they did not use any objective assessments such as pulmonary function tests.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies over the impact of sinusitis on asthma have been mainly about the surgical intervention of sinusitis or done with children patients [28, 29, 30, 31]. In one study, 78% of pediatric patients who suffered from chronic respiratory symptoms more than 3 months and used bronchodilator every day were able to stop the bronchodilator after 2-5 weeks of antibiotic treatment for sinusitis [6].…”
Section: Discussionmentioning
confidence: 99%
“…Senior et al 16 concluded in their study that FESS in 30 patients with CRS and asthma had positive impact in 89.9%, no change was reported in 11.1%, while no patients reported worsening of the subjective measurements for asthma. Regarding objective measurements, 46% reported improvement in bronchodilator inhalers use and 65% reported improvement in oral steroids use.…”
Section: Graph 1: Presentation Of Symptoms In Study and Control Groupmentioning
confidence: 92%